Changes of perceived line orientation during prolonged viewing of tilted lines: The normalization effect - Vaitkevicius, Henrikas; Bliumas, Remigijus; Švegžda, Algimantas; Kulikowski, Janus; Viliunas, Vilius; Stanikunas, Rytis; Dzekevičiūtė, Aldona (Psichologija, 2008)
J. J. Gibson has noted that during prolonged viewing a line perceptually rotates towards the nearest vertical or horizontal meridian. This is known as the normalization effect, but the phenomenon remains poorly investigated. According to our experimental results, the adapting line perceptually rotates to the nearest of three orientations: vertical, horizontal or diagonal. The orientation of these three lines does not change during prolonged viewing. Furthermore, the orientation of lines tilted by either 22.5° or 67.5° does not change subjectively, either. Any changes in the orientation of these lines cause subjective drift towards the nearest vertical, diagonal (oriented by 45°) or horizontal line.
Keywords: line orientation; adaptation; normalization effect